Examining the Correlations Between Industry 4.0 Assets, External and Internal Risk Factors and Business Performance Among Hungarian Food Companies - Erdei, E.; Kossa, G.; Kovács, S.; Popp, J.; Oláh, J (Amfiteatru Economic)
The current maturity of enterprises has a significant development potential for the introduction of new technologies, and requires significant physical, mental and material resources. In this research, we examined the impact of the risk factors of Hungarian food production companies, Industry 4.0 tools, and the supporting and hindering factors affecting the companies, and how they affect changes in business performance. The questionnaire survey took place between 2019 and 2020, during which time we collected data from 276 food companies. The data were then analysed using a number of statistical methods: Cronbach's alpha index, factor analysis, PLS pathway analysis, indicator reliability index, composition reliability index, mean explained variance index, Fornell-Larcker criterion, heterotrait-monotrait ratio, magnitude of effect, fit goodness, predictive relevance, and road model coefficients. In this study we formulated three hypotheses related to Industry 4.0 tools, external and internal risk factors, and business performance, which we were able to accept during the study. By analysing the risk factors, we try to identify the types of external and internal risks that are most characteristic of companies, so that they can react to them as efficiently and quickly as possible, thus making the company effective and efficient at the same time